Management of Pindo palm Syagrus romanzoffiana (Cham.) Glassman, (Arecaceae) to produce Coleoptera edible larvae among the Guaraníes of northeastern Argentina - Araujo, Jorge Justino; Keller, Héctor Alejandro; Hilgert, Norma I. (Ethnobiology and Conservation, 2017)
One of the most important uses of palm trees among Amerindian groups is as a food source as coleopteran larvae are reared on their stems. Guaraní groups settled in the province of Misiones, in northeastern Argentina, consume three species of Curculionidae larvae (Metamasius hemipterus, Rhynchophorus palmarum and Rhinostomus barbirostris), which are bred in the stipes of Syagrus romanzoffiana palm. This work deals with the management of the different ontogenetic stages of this palm to promote the development of the three edible larvae species. Field observation suggests a great knowledge of these insects ecology and of the differential characteristics of the palm tree wood anatomical structure throughout its ontogenetic development. This constitutes the first record of the use of Metamasius hemipterus as food for the Mbya.